2014
DOI: 10.1186/s13041-014-0072-z
|View full text |Cite
|
Sign up to set email alerts
|

Sensitization of neurons in the central nucleus of the amygdala via the decreased GABAergic inhibition contributes to the development of neuropathic pain-related anxiety-like behaviors in rats

Abstract: BackgroundDespite high prevalence of anxiety accompanying with chronic pain, the mechanisms underlying pain-related anxiety are largely unknown. With its well-documented role in pain and emotion processing, the amygdala may act as a key player in pathogenesis of neuropathic pain-related anxiety. Pain-related plasticity and sensitization of CeA (central nucleus of the amygdala) neurons have been shown in several models of chronic pain. In addition, firing pattern of neurons with spike output can powerfully affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
60
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 82 publications
6
60
0
1
Order By: Relevance
“…Analysis of innate anxiety in the behavioural tests used previously revealed that icv R3(B1-22)R (4 nmol; a dose shown to reduce motivated food seeking in mice [44]) increased anxiety-like behaviour in the EPM ( Table 2 In regard to the latter, RXFP3 mRNA is abundantly expressed in several brain areas associated with control of anxiety-like behaviours, including the well characterised extended amygdala [6,[50][51][52]. Relaxin-3 is primarily expressed in GABA neurons, as reflected by the co-expression of relaxin-3 and glutamate decarboxylase immunoreactivity in the rat nucleus incertus [18], which suggests RXFP3 activation may act to reinforce inhibitory signalling on target neurons.…”
Section: Effect Of Icv Rxfp3 Antagonist On Basal Anxiety-like Behaviourmentioning
confidence: 99%
“…Analysis of innate anxiety in the behavioural tests used previously revealed that icv R3(B1-22)R (4 nmol; a dose shown to reduce motivated food seeking in mice [44]) increased anxiety-like behaviour in the EPM ( Table 2 In regard to the latter, RXFP3 mRNA is abundantly expressed in several brain areas associated with control of anxiety-like behaviours, including the well characterised extended amygdala [6,[50][51][52]. Relaxin-3 is primarily expressed in GABA neurons, as reflected by the co-expression of relaxin-3 and glutamate decarboxylase immunoreactivity in the rat nucleus incertus [18], which suggests RXFP3 activation may act to reinforce inhibitory signalling on target neurons.…”
Section: Effect Of Icv Rxfp3 Antagonist On Basal Anxiety-like Behaviourmentioning
confidence: 99%
“…6,16 Evidence accumulated from recent studies has suggested that GABA A receptors in the CeA are involved in pain modulation. For example, intra-CeA administration of muscimol hydrochloride (Mus), a selective GABA A receptors agonist, could inhibit mechanical allodynia, 11,25 whereas intra-CeA application of bicuculline (Bic), a selective GABA A receptor antagonist, showed no influence on mechanical allodynia 25 or induced mechanical hyperalgesia. 11 Nonetheless, several recent studies report contradictory results that indicated that microinjection of Bic and Mus into the CeA increased and decreased antinociceptive response, respectively.…”
mentioning
confidence: 99%
“…GABAergic inhibition has been observed in chronic pain conditions as well. 24 Evidence suggests that treatment with medications for anxiety and insomnia can help alleviate chronic pain. 23,24 Data from this case do not adequately explain the impact of auricular acupuncture on chronic tendinopathy.…”
Section: Discussionmentioning
confidence: 99%
“…24 Evidence suggests that treatment with medications for anxiety and insomnia can help alleviate chronic pain. 23,24 Data from this case do not adequately explain the impact of auricular acupuncture on chronic tendinopathy. The alleviation of pain as a result of exercise and dry needling may have accounted for the reduction in psychosomatic symptoms.…”
Section: Discussionmentioning
confidence: 99%